Foreign Bank Entry and Domestic Banks Performance in China - Liu, Hao (2014)
Chinese bank sector has undergone several reforms following its accession to WTO in 2001. In this thesis, I examine how foreign bank entry would affect the performance of Chinese domestic banks from 2004 to 2011. Both the aggregate level and the individual level of foreign bank ownership measure are used in this study. The results suggest that higher foreign bank ownership is positively related to bank profitability, cost efficiency, loan quality and also income generating capacity. Further, these positive effects are more pronounced for joint-stock commercial banks (JCBs). In the long run, it is essential to take the heterogeneity of banks characteristics into account.